Akútne skrótum je stav vyzadujúci chirurgickú intervenciu - Murár, E; Omaník, P; Funáková, M; Béder, I; Horn, F (Rozhledy v chirurgii, 2008)
UNLABELLED: Acute scrotum (AS) is a clinical syndrome, in which authors indicate a surgical exploration of the scrotum. We retrospectively analyzed the group of 354 patients in 10 years (1997-2006) to compare the preoperative findings with the diagnosis of surgical exploration. The aim was to actualize diagnostics and therapeutic management. PATIENTS AND METHODS: We focused on the age of patients, incidence of nosological units of AS and preoperative and surgical diagnosis. RESULTS: 334 boys were operated on from the whole group - 354 patients. Most frequent incidence of AS was in the age group 8-12 (55%). Torsion of testicular appendix or epididymis is the most frequent cause of AS in our group - 204, 59%. In this group of patients ultrasound confirmed the diagnosis only in 120 patients, 65%. Testicular torsion was managed in 74 boys (30 neonates), in 40 of them we decided, mostly at the second look operation after 48-72 hours, for testicle ablation caused by the organ avitality. In all patients with testicular torsion ultrasound confirmed the diagnosis, 100%. In 10 boys we found testicular tumor. In the group of 334 patients operated on, there were no serious complications. DISCUSSION: Testicular torsion and tumor are the units in which the surgical exploration is performed without discussion. Beside that, torsion of the testicular or epididymic appendix is the most frequent occurring diagnosis. There is a group of surgeons, who performed in this unit conservative management. CONCLUSIONS: after the analysis of the group of our patients we actualized the guidelines used in the management of AS in children. Urgent surgical exploration in boys with AS still seems to be the method of choice.
Keywords: Child; novorozenec; Infant, Newborn; Scrotum; předškolní dítě; Spermatic Cord Torsion; skrotum; Infant; Adolescent; Humans; mužské pohlaví; Male; lidé; Child, Preschool; kojenec; torze semenného provazce; dítě; mladiství